High Frequency Direct Organogenesis Protocol for Mass Multiplication of Centrosema pubescens Benth (Plant Tissue Culture and Biotechnology, 2026)
This study was aimed to develop a suitable protocol for rapid and mass propagation of Centrosema pubescens Benth. Fresh seeds from field grown plants were aseptically cultured on full and half-strength MS media in combination with or without PGRs (plant growth regulators). Cent percent seed germination was achieved on half-strength MS medium without any PGRs and MS medium in combination with 1.0 mg/l BAP. The shoot apices and nodal segments from in vitro grown seedlings were aseptically cultured for direct organogenesis. The MS medium supplemented with 2.0 mg/l BAP + 1.0 mg/l IAA produced maximum number of multiple shoot buds (4.44 ± 0.12) per shoot apices segment. On the other hand, 93% of nodal segments gave response for induction of multiple shoot buds when cultured them on MS medium supplemented with 2.0 mg/1 BAP + 1.0 mg/1 NAA. The highest percentage of leaf segments (86%) produced brownish friable callus on MS + 1.0 mg/l 2, 4-D + 0.5 mg/I BAP. It was reported that brownish friable callus did not undergo any kind of differentiation. Maximum root induction was 5.20 ± 0.10 per elongated shoot and the highest average length 3.07 ± 0.26 cm was observed on half-strength MS medium fortified with 1.0 mg/l IAA. The strong and stout rooted plantlets were successfully hardened with 78% of survival rate. Further research could be initiated to produce secondary metabolites from the friable callus of this plant species to fulfill the demands of the pharmaceutical industries.Plant Tissue Cult. & Biotech. 36(1): 107-116, 2026 (June)